Five principles for deploying and managing Linux in the cloud : with Azure - Alapati, Sam R. (O'Reilly Media, 2018)
A successful migration to the cloud can have a positive impact on the cost, ease of access, maintenance, scalability, elasticity, and versatility of your IT infrastructure. But the migration process itself can be demanding. In this practical ebook, author Sam Alapati examines five principles for deploying and managing your Linux-based system in the cloud. There are many half-baked truths and pitfalls in cloud computing, and without thorough assessments and planning, your migration can lead to excessive costs in time and money. Using examples from Azure Cloud Services and other providers, this ebook demonstrates best practices for moving your system out of your data center and into the cloud. DevOps engineers and system administrators also get a detailed overview of the various types of cloud services and deployments available. By learning these five cloud migration principles, your team will be able to: Assess and identify which Linux virtual machines are adaptable in the cloud Determine and plan for your workload's level of availability for new deployments Monitor your applications running on Linux across the entire stack Ensure your Linux virtual machines are secure and backed up Govern your cloud environment using policy management best practices.